Rinite alérgica - Mion, Olavo; Di Francesco, Renata Cantisani; Amato, Flávia Silveira; Chi Sakai, Andrea Peiyun [UNESP] (My University, 2014)
Allergic rhinitis is a common chronic disease that affects people of different ages in all parts of the world. Although not life threatening, can greatly compromise the quality of life of the affected individual. Diagnosis is by clinical history, physical examination and laboratory tests. Treatment of rhinitis is complex since it involves several steps such as awareness through educational measures, environmental control, medication use, surgical procedures and other therapies. This update aims to address a practical way how to diagnose, classify and and treat allergic rhinitis.
Allergic rhinitis